PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI - Nurul Miftahul Azizah (AmaNU: Jurnal Manajemen dan Ekonomi, 2023)
This study aims to determine the effect of leadership style and organizational culture on employee performance at the Department of Trade, Cooperatives, Small and Medium Enterprises, Cilacap Regency. So the objectives to be achieved in this study are: 1) To determine the effect of Leadership Style on Employee Performance at the DPKUKM Office of Cilacap Regency. 2) To determine the influence of Organizational Culture on Employee Performance at the DPKUKM Office of Cilacap Regency. 3) To determine the simultaneous influence of Leadership Style and Organizational Culture on Employee Performance at the DPKUKM Office of Cilacap Regency. The results of this study indicate that: 1) Leadership style has a positive effect on employee performance at the Department of Trade, Cooperatives, Small and Medium Enterprises, Cilacap Regency. 2) Organizational Culture has a positive effect on Employee Performance at the Office of Trade, Cooperatives, Small and Medium Enterprises of Cilacap Regency. 3) Leadership Style and Organizational Culture simultaneously influence Employee Performance.